El principio del patrimonio común de la humanidad y el acuerdo BBNJ - Scovazzi, Tullio (Pontificia Universidad Católica del Perú, 2025)
Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas beyond National Jurisdiction (New York, 2023) it addresses marine biodiversity under the perspective of four subject-matters: marine genetic resources, area-based management tools, environmental impact assessment and transfer of marine technologies. This article takes in consideration only the first subject, which involves two fundamental principles of international law of the sea, one having a consolidated tradition (the freedom of the sea) and the other having an innovating character (the common heritage of humankind).

El Acuerdo sobre la Conservación y el Uso Sostenible de la Diversidad Biológica Marina de las Zonas Fuera de la Jurisdicción Nacional (Nueva York, 2023) aborda la biodiversidad marina desde la perspectiva de cuatro temas: recursos genéticos marinos, herramientas de gestión basadas en áreas, evaluación del impacto ambiental y transferencia de tecnologías marinas. Este artículo se centra únicamente en el primer tema, que abarca dos principios fundamentales del derecho internacional del mar: uno con una tradición consolidada (la libertad del mar) y el otro con un carácter innovador (el patrimonio común de la humanidad).
The principle of common heritage of humankind and the BBNJ agreement
Keywords: Common heritage of humankind; BBNJ agreement; Agreement on Marine Biological Diversity of Areas beyond National Jurisdiction; Patrimonio común de la humanidad; BBNJ Agreement; Acuerdo sobre la Diversidad Biológica Marina de las Zonas Fuera de la Jurisdicción Nacional; https://purl.org/pe-repo/ocde/ford#5.09.01